Pengaruh Digital Marketking melalui Sosial Media Instagram dan Brand Image terhadap Minat Menggunakan Aplikasi Olin - Januarto Januarto (Journal of Management and Bussines (JOMB), 2024)
The research aims to test and analyze the influence of digital marketing through Instagram social media and brand image on interest in using applications. This research uses a positivistic paradigm approach, with a quantitative type of research. This research involved 100 respondents taken through purposive sampling. The data analysis used is multiple linear regression analysis with SPSS. The research results show that digital marketing partially influences interest in using the OLIN application, this is shown by tcount of 9,040 > ttable 1,985, with a significance level of 0.000 < α 0.05. Likewise, brand image partially influences interest in using the OLIN application as shown by tcount of 3.783 > ttable 1.985 with a significance level of 0.000 < α 0.05. Simultaneously, digital marketing through social media Instagram and brand image influence interest in using the OLIN application, as shown by the f count of 274,929 > f table 3,089 and a significance level of 0.000 < α 0.05. The coefficient of determination is 0.850, which indicates that interest in using the OLIN application is influenced by digital marketing via social media Instagram and brand image by 85%, and the remaining 15% is influenced by other variables not examined in this research. The contribution from digital marketing is 61.15% and the brand image contribution is 23.91%. The conclusion is that digital marketing through Instagram social media and brand image, both partially and simultaneously, have a positive and significant influence on interest in using the OLIN application, where the contribution of digital marketing through Instagram social media is more dominant than brand image. Keywords: Digital Marketing, Social Media, Instagram, Brand Image, Consumer Interest